2016
DOI: 10.1139/apnm-2015-0702
|View full text |Cite
|
Sign up to set email alerts
|

Short-term high-fat diet alters postprandial glucose metabolism and circulating vascular cell adhesion molecule-1 in healthy males

Abstract: Short-term intake of a high-fat diet aggravates postprandial glucose metabolism; however, the dose-response relationship has not been investigated. We hypothesized that short-term intake of a eucaloric low-carbohydrate/high-fat diet (LCHF) would aggravate postprandial glucose metabolism and circulating adhesion molecules in healthy males. Seven healthy young males (mean ± SE; age: 26 ± 1 years) consumed either a eucaloric control diet (C, approximately 25% fats), a eucaloric intermediate-carbohydrate/intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Previous LCHF studies show conflicting results for FFA suppression during a glucose load. A 72-h LCHF (fat E% 69) showed complete suppression of lipolysis during an OGTT (Numao et al, 2016). Another 69-h LCHF study (fat E% 83) showed a reduced suppression of lipolysis during an intravenous glucose tolerance test (IVGTT) (Johnson et al, 2006) with a similar FFA decrease as in the current study.…”
Section: Ffa and 3-ohbsupporting
confidence: 74%
See 1 more Smart Citation
“…Previous LCHF studies show conflicting results for FFA suppression during a glucose load. A 72-h LCHF (fat E% 69) showed complete suppression of lipolysis during an OGTT (Numao et al, 2016). Another 69-h LCHF study (fat E% 83) showed a reduced suppression of lipolysis during an intravenous glucose tolerance test (IVGTT) (Johnson et al, 2006) with a similar FFA decrease as in the current study.…”
Section: Ffa and 3-ohbsupporting
confidence: 74%
“…Previous human studies have shown negative effects of lipid infusion on glucose tolerance (Itani et al, 2002;Hoeg et al, 2011;Hoeks et al, 2012). A higher availability of fatty acids in seen in the blood after an intravenous lipid infusion (≈1.3-2.2 mmol/L), compared to blood levels of fatty acids in studies with LCHF diets without infusion (≈ 0.45 mmol/L) (Numao et al, 2016). A high intake of fat without weight-gain induces insulin resistance in rodents (Jornayvaz et al, 2010;Kinzig et al, 2010), whereas a recent human study showed that a 6 week LCHF diet with 64 percentage of energy (E%) fat, did not decrease insulin sensitivity in slightly overweight males (Lundsgaard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kolmogorov-Smirnov tests were used to check the normality of distributions for all blood parameters. Based on the distribution of postprandial glucose values in our previous studies, the sample size was calculated to detect a large effect (Cohen's d = 0.98) [31,32]. The calculated sample size of 11 was required to approximately have 80% power to detect large effects at a significance level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…When significant interaction effects were detected, we used the Bonferroni method for post-hoc comparisons. Based on the distribution of postprandial glucose values in our previous study, the sample size was calculated to be able to detect a large effect (Cohen’s d = 0.98) [ 16 , 37 ]. Power analysis demonstrated that a sample size of 11 would be required to have approximately 80% power to detect a large effect at a significance level of 0.05.…”
Section: Methodsmentioning
confidence: 99%